(untitled) (Research, Society and Development, 2022)
The Covid-19 pandemic changed the lives of many people, caused countless deaths and brought a series of problems to all countries, not only in the area of public health, but also in various sectors, impacting, directly and indirectly, the survival of various populations. This article portrays some of this problem, specifically with regard to the increase in the number of wills made in Brazil during the first months of the disease in 2020. The objective of the work is also to address the different types of wills present in the Brazilian Civil Code 2002 and, in a very objective way, try to explain when each type can be used. For that, a broad bibliographical research was carried out, through doctrines and articles published on the internet on the subject in question. Therefore, the work brings a reflection on what can be improved to reduce the formalities in the preparation of wills and clarify the various types of wills and what is most appropriate for each situation.